The Effects of Workforce Competence and Total Quality Management on Employee Performance in the Textile Industry in West Java - Yuyus Yudistria; Luluh Abdilah Kurniawan; Atty Tri Juniarti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study investigates the direct and indirect effects of workforce competence and Total Quality Management (TQM) implementation on employee performance in the textile and textile products (TPT) industry in West Java. Using a survey of 328 employees across major TPT firms, data were collected through structured questionnaires and interviews and analyzed with path analysis to quantify causal relationships. Results indicate that workforce competence directly improves employee performance by 26.32% and indirectly through TQM by 17.57%, contributing a total of 43.89%. Meanwhile, TQM shows a direct impact of 16.81% and a stronger indirect effect through motivation of 34.38%, highlighting its central role in enhancing employee outcomes. Together, competence and TQM account for 78.3% of performance variation, underscoring their synergistic influence in driving productivity and quality. The findings imply that investing in employee training to strengthen technical and operational competencies, alongside adopting TQM practices such as continuous improvement and employee empowerment, can significantly improve performance. This study contributes to the management literature by clarifying how competence and TQM interact in a skill-intensive and competitive industry context. Limitations include its regional focus and reliance on self-reported data. Future research should extend the scope to other industries and incorporate additional organizational factors.